Pelayanan Publik Kantor Camat Rambah Hilir Kabupaten Rokan Hulu - Silvia Rahmi; Hendry Andry (UIR Press, 2019)
This study aims to determine public services at the Rambah Hilir Sub-District Office, Rambah Hilir District, Rokan Hulu Regency. Indicators of public assessment include service requirements, service procedures, service times, service costs, service products, and complaint handling. Quantitative methods, namely prioritizing questionnaires as a data collection tool, and the data collected with this tool is then used as the main raw material to analyze the empirical conditions of the objective objectives of research objectives at meticulous locations. There are 5 populations and the sample in this study is employees / officers and the community totaling 70 people, the community is 50 people and the employees are 20 people, then the Camat, the Secretary of the Subdistrict, and the Head of Services as the sample interviewed. The technique used in this study is the incident sampling technique for all respondents. Types and data collection techniques consist of primary data collected by questionnaire and interview list techniques and secondary data using observation techniques. While the analysis techniques of the researchers were used with the help of frequency, based on this analysis the researchers concluded that public services at the Rambah Hilir Sub-District Office, Rambah Hilir Subdistrict, Rokan Hulu Regency were at a fairly good interval. Recommendations that need to be considered are mainly regarding procedures, requirements and service providers that must be improved again so that the community feels satisfied with the services provided.